Imaging Retinal Blood Flow with Laser Speckle Flowmetry - Srienc, Anja I.; Kurth-Nelson, Zeb L.; Newman, Eric (Frontiers in Neuroenergetics, 2010)
Laser speckle flowmetry (LSF) was initially developed to measure blood flow in the retina. More recently, its primary application has been to image baseline blood flow and activity-dependent changes in blood flow in the brain. We now describe experiments in the rat retina in which LSF was used in conjunction with confocal microscopy to monitor light-evoked changes in blood flow in retinal vessels. This dual imaging technique permitted us to stimulate retinal photoreceptors and measure vessel diameter with confocal microscopy while simultaneously monitoring blood flow with LSF. We found that a flickering light dilated retinal arterioles and evoked increases in retinal blood velocity with similar time courses. In addition, focal light stimulation evoked local increases in blood velocity. The spatial distribution of these increases depended on the location of the stimulus relative to retinal arterioles and venules. The results suggest that capillaries are largely unresponsive to local neuronal activity and that hemodynamic responses are mediated primarily by arterioles. The use of LSF to image retinal blood flow holds promise in elucidating the mechanisms mediating functional hyperemia in the retina and in characterizing changes in blood flow that occur during retinal pathology.